Crime Prevention Practice Paper 2: An Overview to Alcohol Free Zones and Alcohol Prohibited Areas in NSW Councils - Chiu, Dave Yue Kim (2011)
To prevent anti‐social behaviour associated with alcohol consumption and improve public safety, NSW councils have been given the legislative power to manage the consumption of alcohol in public spaces through establishing Alcohol Free Zones (AFZs) and Alcohol Prohibited Areas (APAs). This paper provides information about the following: What are Alcohol Free Zones and Alcohol Prohibited Areas?; Examples of AFZ and APA signs; Establishment procedures and law enforcement powers; Council approaches to AFZs and APAs; Useful resources